Cytogenetic characterization of head and neck squamous cell carcinoma cell lines as model systems for the functional analyses of tumor-associated genes - Freier, Kolja; Hofele, Christof; Knöpfle, Karl; Gross, Madeleine; Devens, Frauke; Dyckhoff, Gerhard; Plinkert, Peter K.; Lichter, Peter; Herold-Mende, Christel (Journal of oral pathology & medicine, 2010)
J Oral Pathol Med (2010) 39: 382-389 Head and neck squamous cell carcinoma (HNSCC) is a solid malignant neoplasm exhibiting aggressive phenotypes and high recurrence rates. To improve its clinical management, understanding the molecular basis of HNSCC development is of critical importance. For the investigation of tumor-associated genes, functional analyses in well-characterized tumor cell systems are required. To establish an experimental platform, a set of 20 HNSCC cell lines was screened for genetic imbalances by chromosomal comparative genomic hybridization (cCGH). Frequent DNA copy number gains were detected on 3q26.3-qter, 5p, 7p11-p13, 8q23-qter, 9p11-p13, 9q31-qter, 11q13 and 20q13.1, whereas copy number losses were found on 3p, 4p, 4q32.1-qter, 8p11-p12 and 18q22 in agreement with previous observations on genetic aberrations detected in primary HNSCC specimens. Subsequent mRNA expression analysis of 11q13 candidate genes CCND1 and CTTN revealed that HNSCC cell lines exhibiting a DNA copy number gain on 11q13 had a higher transcript level of CCND1 and CTTN compared with HNSCC cell lines without 11q13 copy number gain (P = 0.014 and P = 0.009, respectively). Furthermore, CCND1 and CTTN amplification as detected by fluorescence in situ hybridization correlated with protein expression as assessed by immunocytochemistry. In summary, the cytogenetic characterization illustrates that this set of HNSCC cell lines is representative for the HNSCC genome and provides tumor model systems for detailed analysis of genes with a possible role in the pathomechanism of head and neck tumors.
Gesehen am 19.06.2023